A novel dominant selectable system for the selection of transgenic plants under in vitro and greenhouse conditions based on phosphite metabolism. Issue 4 (27th March 2013) - López‐Arredondo, Damar L.; Herrera‐Estrella, Luis
Summary Antibiotic and herbicide resistance genes are currently the most frequently used selectable marker genes for plant research and crop development. However, the use of antibiotics and herbicides must be carefully controlled because the degree of susceptibility to these compounds varies widely among plant species and because they can also affect plant regeneration. Therefore, new selectable marker systems that are effective for a broad range of plant species are still needed. Here, we report a simple and inexpensive system based on providing transgenic plant cells the capacity to convert a nonmetabolizable compound (phosphite, Phi) into an essential nutrient for cell growth (phosphate) trough the expression of a bacterial gene encoding a phosphite oxidoreductase (PTXD). This system is effective for the selection of Arabidopsis transgenic plants by germinating T0 seeds directly on media supplemented with Phi and to select transgenic tobacco shoots from cocultivated leaf disc explants using nutrient media supplemented with Phi as both a source of phosphorus and selective agent. Because the ptxD/Phi system also allows the establishment of large‐scale screening systems under greenhouse conditions completely eliminating false transformation events, it should facilitate the development of novel plant transformation methods.